The Role of Spatial Experience Fixation and Invisible Assumptions on the Designs of First Year Students of Architecture - Erkan Yazıcı, Yasemin (My University, 2011)
Spatial experiences are invaluable for expanding a designer's design vocabulary, however, a firm attachment to these definitions or preconceptions can curb a designer's ability to come up with new and innovative design solutions. One of the primary aims of the first year architectural design education is to dissolve students' tendencies to use these preconceptions and fixed definitions in their designs. Therefore, design methods that promote alternative and flexible thinking as well as encourage students to reflect on their own design processes are used in the first year of architectural education, in order to reduce the adverse effects of stereotyped ideas and preconceptions This paper reports an experimental study conducted with the voluntary participation of 20 beginning students of architecture enrolled in the Department of Architecture of Istanbul Kültür University, to investigate the effects of spatial experience, invisible assumptions and fixation on the designs of first year architecture students. Another aim of this study was to motivate beginning architectural students to carry out a self-analysis of their own design processes and to demonstrate the effect of preconceptions on their designs.
Keywords: SPATIAL EXPERIENCE; INVISIBLE ASSUMPTIONS; DESIGN FIXATION; FIRST YEAR ARCHITECTURAL EDUCATION